A method for preparing superstructured carbon nanotube absorbing material
By covering polyimide on the outer surface of MoO3 nanorods and etching and carbonizing, superstructured carbon nanotube absorbing materials were prepared, solving the problems of easy agglomeration and impedance mismatch of existing carbon nanotube materials, and achieving efficient electromagnetic wave absorption performance.
Patent Information
- Application Number
- CN202411056887.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-02
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-08-02
AI Technical Summary
Existing carbon nanotube materials are prone to agglomeration and mismatched impedances, which affects their electromagnetic absorption performance.
The superstructured carbon nanotube absorbing material is formed by coating polyimide on the outer surface of the MoO3 nanorod and etching and carbonization. The method includes stirring ammonium molybdate tetrahydrate with nitric acid solution at room temperature, then adding it to the mixture for ultrasonic treatment, condensation and reflux, washing and drying, and finally calcining at high temperature under a nitrogen atmosphere to obtain a superstructured carbon nanotube absorbing material.
The formed superstructured carbon nanotube material has good dispersion and impedance matching characteristics, which significantly improves its electromagnetic wave absorption performance and can effectively absorb bandwidths with reflection loss intensity less than -10 dB.
Smart Images

Figure CN118894523B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electromagnetic absorbing materials, and in particular relates to a method for preparing a superstructure carbon nanotube absorbing material. Background Art
[0002] The progress of science and technology has promoted the rapid development of electronics, electrical equipment and radio communications. The popularization of these equipment has brought great convenience to human production and life, but at the same time, the increasingly serious electromagnetic pollution has become a problem that cannot be ignored. In addition, in order to achieve radar stealth of military targets, ensure the safety of military targets, improve the combat effectiveness and combat life of weapons and equipment to adapt to the battlefield needs under information conditions, effective electromagnetic protection measures have extremely important strategic significance for national defense security. In summary, electromagnetic protection materials play an important role in all fields of the national economy and national defense construction. Electromagnetic wave absorbing materials can convert electromagnetic energy into other forms of energy such as heat energy and consume it, fundamentally alleviating electromagnetic pollution. In recent years, various electromagnetic wave absorbing materials, such as magnetic metals / ferrites, metal oxides / sulfides, conductive polymers, carbon materials, etc., have been widely used in the prevention and elimination of electromagnetic pollution. Carbon nanotubes benefit from their high conductivity and large vertical and horizontal surface area, which makes them have very strong dielectric loss capacity, low density and high chemical stability, and have potential applications in the field of electromagnetic wave absorption. Studies have found that the structure of carbon nanotubes has a very important influence on their electromagnetic absorption performance. Recently, researchers have prepared core-shell carbon nanotubes, scabbard carbon nanotubes and helical carbon nanotubes, and these structured carbon nanotubes have strong attenuation characteristics for incident electromagnetic waves. However, these prepared materials show serious agglomeration, which is not conducive to performance reproducibility. Summary of the invention
[0003] Aiming at the problems of easy agglomeration and impedance mismatch of carbon nanotubes prepared in the prior art, the present invention provides a method for preparing a superstructure carbon nanotube absorbing material.
[0004] The present invention adopts the following technical solution:
[0005] A method for preparing a superstructured carbon nanotube absorbing material, the present invention coats the outer surface of MoO3 nanorods with polyimide, and obtains the superstructured carbon nanotube absorbing material by etching and carbonization. The preparation method specifically comprises the following steps:
[0006] In the first step, ammonium molybdate tetrahydrate is added to a nitric acid solution and stirred at room temperature at a stirring speed of 3000 r / min to obtain a uniform solution;
[0007] The second step is to mix anhydrous ethylenediamine, N,N-dimethylformamide and pyromellitic anhydride in proportion to obtain a mixed solution, add the uniform solution obtained in the first step to the mixed solution, perform ultrasonic treatment, then transfer the mixture into a round-bottom flask, condense and reflux at 165° C., centrifuge, wash, and dry to obtain an intermediate product;
[0008] The third step is to put the intermediate product obtained in the second step into ammonia water, stir, wash, and dry to obtain a white powder;
[0009] In the fourth step, the white powder obtained in the third step is subjected to high-temperature calcination and carbonization in a nitrogen atmosphere to obtain a superstructure carbon nanotube absorbing material.
[0010] Furthermore, in the first step, the usage ratio of the ammonium molybdate tetrahydrate to the nitric acid solution is 0.05-0.09 g: 17-21 mL.
[0011] Furthermore, in the second step, the usage ratio of anhydrous ethylenediamine, N,N-dimethylformamide and pyromellitic anhydride is 0.576-0.580 g: 58-62 mL: 2.119-2.123 g.
[0012] Furthermore, in the second step, the ultrasonic frequency is 30 KHz, the ultrasonic time is 1-2 hours; the drying temperature is 60° C., the drying time is 4 hours; the reflux environment is alkaline conditions, and the reflux time is 6 hours.
[0013] Furthermore, the mass concentration of the ammonia water in the third step is 6%, the dosage is 23-27 mL, and the stirring time is 12 h. Among them, the ammonia water treatment can remove MoO3.
[0014] Furthermore, in the third step, the drying temperature is 70° C. and the drying time is 6 hours; and the washing is carried out using deionized water and ethanol in sequence.
[0015] Furthermore, the carbonization process in the fourth step is to control the heating rate to 5°C / min, the calcination temperature to 800°C, and the calcination time to 2h.
[0016] In the superstructured carbon nanotube microwave absorbing material formed by the method provided by the present invention, since the surface of the carbon nanotube is formed by orderly assembly of carbon nanosheets, the good dispersion of the carbon nanotubes is ensured. In addition, the carbon nanosheets on the surface of the carbon nanotubes are assembled into an orderly mesoporous structure, which suppresses the skin current on the surface of the carbon nanotubes and significantly improves the impedance matching of the material.
[0017] The superstructured carbon nanotubes prepared by the present invention can be used in an electromagnetic wave absorber. The absorber includes a superstructured carbon nanotube electromagnetic wave absorbing material and paraffin. The mass percentage of the superstructured carbon nanotube electromagnetic wave absorbing material in the absorber can be adjusted according to actual needs.
[0018] Preferably, the mass fraction of the superstructured carbon nanotube electromagnetic wave absorbing material in the absorber is 10%. At this filler ratio, the frequency range in which the reflection loss intensity is less than -10 dB is 5.4-18.0 GHz.
[0019] The beneficial effects of the present invention are:
[0020] (1) In the prepared superstructured carbon nanotubes, the surface of the carbon nanotubes is assembled from carbon nanosheets, forming ordered mesopores, which ensures the good dispersion of the nanotubes.
[0021] (2) In the prepared superstructured carbon nanotubes, the formation of an ordered mesoporous structure on the surface of the carbon nanotubes significantly improves the impedance matching of the material.
[0022] (3) The absorber has excellent wave absorption performance and can effectively absorb reflection loss with a bandwidth less than -10 dB. The prepared absorber has thin thickness, low density and high absorption intensity. It has broad application prospects in electromagnetic wave absorption in the field of communication technology, prevention of electromagnetic leakage, and electromagnetic protection of high-precision instruments.
[0023] The superstructured carbon nanotubes prepared by the present invention have good dispersibility and excellent impedance matching characteristics. The maximum reflection loss can reach -66.0 dB. When the thickness of the absorber is 1.7 mm, the bandwidth in which the reflection loss is less than -10 dB can reach about 5.6 GHz, ranging from 12.4 to 18.0 GHz.
[0024] In summary, the present invention prepares a superstructured carbon nanotube electromagnetic wave absorption material with good impedance matching characteristics. The self-assembly of carbon nanosheets on the surface of carbon nanotubes ensures their good dispersibility. In the obtained superstructured carbon nanotubes, the formation of an ordered mesoporous carbon structure on the surface of the carbon nanotubes significantly improves the impedance matching characteristics of the material, making the material have broad application prospects in electromagnetic absorption.
[0025] The material prepared by the invention is used for making a light and efficient wave absorbing coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a scanning electron microscope image of the superstructured carbon nanotube absorbing material prepared in Example 1;
[0027] Figure 2 Transmission electron microscope images of the superstructured carbon nanotube absorbing material prepared in Example 1 at different magnifications;
[0028] Figure 3The XRD graphs of the superstructured carbon nanotube absorbing material and the comparative sample prepared in Example 1, wherein curve a is the XRD of the comparative sample; curve b is the XRD of the superstructured carbon nanotube absorbing material;
[0029] Figure 4 The Raman spectra of the superstructure nanotube absorbing material prepared in Example 1 and the comparative sample, wherein curve a is the Raman spectrum of the comparative sample; curve b is the Raman spectrum of the superstructure carbon nanotube electromagnetic wave absorbing material;
[0030] Figure 5 The graph is a real part curve of the dielectric constant of the superstructured nanotube absorbing material prepared in Example 1 and a comparative sample, wherein curve a is a real part curve of the dielectric constant of the comparative sample; curve b is a real part curve of the dielectric constant of the superstructured carbon nanotube absorbing material;
[0031] Figure 6 The graph is a graph of the imaginary part of the dielectric constant of the superstructured carbon nanotube absorbing material prepared in Example 1 and a comparative sample, wherein curve a is a curve of the imaginary part of the dielectric constant of the comparative sample; curve b is a curve of the imaginary part of the dielectric constant of the superstructured carbon nanotube absorbing material;
[0032] Figure 7 The Δ function diagrams of the superstructured carbon nanotube absorbing material prepared in Example 1 and the comparative sample are shown in FIG. (a) is the Δ function diagram of the comparative sample; FIG. (b) is the Δ function diagram of the superstructured nanotube absorbing material;
[0033] Figure 8 The wave impedance curves of the superstructure carbon nanotube absorbing material and the comparative sample prepared in Example 1, a is the wave impedance curve of the comparative sample; b is the wave impedance curve of the superstructure carbon nanotube electromagnetic wave absorbing material;
[0034] Fig. 9 This is a three-dimensional graph of the reflection loss of the superstructured carbon nanotube absorbing material prepared in Example 1. DETAILED DESCRIPTION
[0035] The present invention is further described in conjunction with specific embodiments.
[0036] Example 1
[0037] A method for preparing a superstructured carbon nanotube absorbing material comprises the following steps:
[0038] Step 1: Add 0.07 g of ammonium molybdate tetrahydrate into 19 mL of nitric acid solution and stir at room temperature at a stirring speed of 3000 r / min to obtain a uniform solution;
[0039] Step 2: Add the homogeneous solution obtained in the first step to a mixture of anhydrous ethylenediamine, N,N-dimethylformamide and pyromellitic anhydride, perform ultrasonic treatment, control the ultrasonic frequency to 30 KHz, and the ultrasonic time to 1.5 h, then transfer to a round-bottom flask, condense and reflux at 165 ° C for 6 h, centrifuge, wash with deionized water, and dry at 60 ° C for 6 h to obtain an intermediate product;
[0040] The mixed solution is a mixed solution of 0.578 g of anhydrous ethylenediamine, 60 mL of N,N-dimethylformamide and 2.121 g of pyromellitic anhydride;
[0041] Step 3: Place the intermediate product obtained in step 2 into 25 mL of 6% ammonia water and stir for 12 h, wash with deionized water and ethanol in sequence, and dry at 70°C for 6 h to obtain a white powder;
[0042] The fourth step is to place the white powder obtained in the third step into a tubular furnace and perform high-temperature calcination in a nitrogen atmosphere, control the heating rate to 5 °C / min, the calcination temperature to 800 °C, and the calcination time to 2 h to obtain the superstructure carbon nanotube absorbing material.
[0043] Comparative Example
[0044] The comparative sample is Example 1, except that the calcination process is changed, the calcination temperature is 700°C, and the calcination time is still 5 h.
[0045] Figure 1 This is a scanning electron microscope image of the superstructure carbon nanotubes prepared in Example 1; it can be seen from the image that the obtained carbon nanotubes are not entangled together and have good dispersion.
[0046] Figure 2 This is a transmission electron microscope image of the superstructured carbon nanotube prepared in Example 1; it can be seen from the figure that the surface of the obtained carbon nanotube is assembled by nanosheets, and the assembly between the nanosheets forms ordered mesopores on the surface of the carbon nanotube. The introduction of ordered surface mesopores can effectively improve the impedance matching characteristics of the material.
[0047] Figure 3 The XRD graphs of the superstructured carbon nanotube absorbing material and the comparative sample prepared in Example 1, wherein curve a is the XRD of the comparative sample; curve b is the XRD of the superstructured carbon nanotube absorbing material. By comparing the X-ray diffraction standard card, it can be seen that although the superstructured carbon nanotube absorbing material and the comparative sample both contain the diffraction peak of graphite carbon, the diffraction peak of the comparative sample is significantly weaker than that of the superstructured carbon nanotube electromagnetic wave absorbing material, indicating that the graphitization degree of the superstructured carbon nanotube electromagnetic wave absorbing material is higher than that of the comparative sample.
[0048] Figure 4 The Raman spectra of the superstructured carbon nanotube absorbing material prepared in Example 1 and the comparative sample, curve a in the figure is the Raman spectrum of the comparative sample; curve b is the Raman spectrum of the superstructured carbon nanotube electromagnetic wave absorbing material. I D / I G The value is higher than that of the comparison sample I D / I G The large value further indicates that the graphitization degree of the superstructure carbon nanotube absorbing material is higher than that of the comparison sample.
[0049] Figure 5 The graph is a real part curve of the dielectric constant of the superstructured carbon nanotube absorbing material prepared in Example 1 and the comparative sample, wherein curve a is the real part curve of the dielectric constant of the comparative sample; curve b is the real part curve of the dielectric constant of the superstructured carbon nanotube absorbing material. It can be seen from the graph that the real part value of the dielectric constant of the superstructured carbon nanotube absorbing material is higher than that of the comparative sample, because the graphitization degree of the superstructured carbon nanotube absorbing material is higher than that of the comparative sample.
[0050] Figure 6 The graph is a graph of the imaginary part of the dielectric constant of the superstructured carbon nanotube absorbing material prepared in Example 1 and the comparative sample, wherein curve a is the imaginary part of the dielectric constant of the comparative sample; curve b is the imaginary part of the dielectric constant of the superstructured carbon nanotube absorbing material. It can be seen from the graph that the imaginary part of the dielectric constant of the superstructured carbon nanotube absorbing material is higher than that of the comparative sample, because the introduction of ordered mesopores on the surface of the carbon nanotubes improves the conductivity of the material.
[0051] Figure 7 The Δ function graphs of the superstructured carbon nanotube absorbing material prepared in Example 1 and the comparative sample are shown in Figure (a) for the comparative sample and Figure (b) for the superstructured carbon nanotube absorbing material. It can be seen from the figure that the area below 0.4 in the Δ function graph of the superstructured carbon nanotube absorbing material is much larger than the area below 0.4 in the Δ function graph of the comparative sample, indicating that the introduction of ordered mesopores on the surface of carbon nanotubes can significantly improve the impedance matching characteristics of the material.
[0052] Figure 8The wave impedance curves of the superstructured carbon nanotube absorbing material and the comparative sample prepared in Example 1 are shown in Figure a, which is the wave impedance curve of the comparative sample; and b is the wave impedance curve of the superstructured carbon nanotube absorbing material. It can be seen from the figure that the wave impedance value of the superstructured carbon nanotube absorbing material is higher than that of the comparative sample, further indicating that the introduction of ordered mesopores on the surface of carbon nanotubes can significantly improve the impedance matching characteristics of the material.
[0053] Fig. 9 The three-dimensional graph of reflection loss of the superstructure carbon nanotube absorbing material prepared in Example 1, wherein the frequency is 2.0~18.0 GHz and the thickness is 1.0~5.0 mm. It can be seen from the figure that the maximum reflection loss value of the superstructure carbon nanotube material is -66.0 dB at a frequency of 17.2 GHz; and when the thickness is in the range of 1.0~5.0 mm, the frequency band in which its reflection loss is less than -10 dB is 5.4~18.0 GHz (about 12.6 GHz), which can achieve C-band, X-band and Ku-band coverage, indicating that the superstructure absorbing material has excellent electromagnetic wave absorption capability.
[0054] Example 2
[0055] A method for preparing a superstructured carbon nanotube absorbing material comprises the following steps:
[0056] Step 1: Add 0.05 g of ammonium molybdate tetrahydrate into 17 mL of nitric acid solution and stir at room temperature at a stirring speed of 3000 r / min to obtain a uniform solution;
[0057] Step 2: Add the homogeneous solution obtained in the first step to a mixture of anhydrous ethylenediamine, N,N-dimethylformamide and pyromellitic anhydride, perform ultrasonic treatment, control the ultrasonic frequency to 30 KHz, and the ultrasonic time to 1.5 h, then transfer to a round-bottom flask, condense and reflux at 165 ° C for 6 h, centrifuge, wash with deionized water, and dry at 60 ° C for 6 h to obtain an intermediate product;
[0058] The mixed solution is a mixed solution of 0.576 g of anhydrous ethylenediamine, 58 mL of N,N-dimethylformamide and 2.119 g of pyromellitic anhydride;
[0059] Step 3: Place the intermediate product obtained in step 2 into 23 mL of 6% ammonia water and stir for 12 h, wash with deionized water and ethanol in sequence, and dry at 70°C for 6 h to obtain a white powder;
[0060] The fourth step is to place the white powder obtained in the third step into a tubular furnace and perform high-temperature calcination in a nitrogen atmosphere, control the heating rate to 5 °C / min, the calcination temperature to 800 °C, and the calcination time to 2 h to obtain the superstructure carbon nanotube absorbing material.
[0061] Example 3
[0062] A method for preparing a superstructured carbon nanotube absorbing material comprises the following steps:
[0063] Step 1: Add 0.09 g of ammonium molybdate tetrahydrate into 21 mL of nitric acid solution and stir at room temperature at a stirring speed of 3000 r / min to obtain a uniform solution;
[0064] Step 2: Add the homogeneous solution obtained in the first step to a mixture of anhydrous ethylenediamine, N,N-dimethylformamide and pyromellitic anhydride, perform ultrasonic treatment, control the ultrasonic frequency to 30 KHz, and the ultrasonic time to 1.5 h, then transfer to a round-bottom flask, condense and reflux at 165 ° C for 6 h, centrifuge, wash with deionized water, and dry at 60 ° C for 6 h to obtain an intermediate product;
[0065] The mixed solution is a mixed solution of 0.580 g of anhydrous ethylenediamine, 62 mL of N,N-dimethylformamide and 2.123 g of pyromellitic anhydride;
[0066] Step 3: Place the intermediate product obtained in step 2 into 27 mL of 6% ammonia water and stir for 12 h, wash with deionized water and ethanol in sequence, and dry at 70°C for 6 h to obtain a white powder;
[0067] The fourth step is to place the white powder obtained in the third step into a tubular furnace and perform high-temperature calcination in a nitrogen atmosphere, control the heating rate to 5 °C / min, the calcination temperature to 800 °C, and the calcination time to 2 h to obtain the superstructure carbon nanotube absorbing material.
Claims
1. A method for preparing a superstructured carbon nanotube absorbing material, characterized in that: The steps include: In the first step, ammonium molybdate tetrahydrate is added to a nitric acid solution and stirred at room temperature at a stirring speed of 3000 r / min to obtain a uniform solution; The second step is to mix anhydrous ethylenediamine, N,N-dimethylformamide and pyromellitic anhydride in proportion to obtain a mixed solution, add the uniform solution obtained in the first step to the mixed solution, perform ultrasonic treatment, then transfer the mixture into a round-bottom flask, condense and reflux at 165° C., centrifuge, wash, and dry to obtain an intermediate product; The third step is to put the intermediate product obtained in the second step into ammonia water, stir, wash, and dry to obtain a white powder; The fourth step is to calcine and carbonize the white powder obtained in the third step at a high temperature under a nitrogen atmosphere to obtain a superstructure carbon nanotube absorbing material; The carbonization process in the fourth step is to control the heating rate to 5°C / min, the calcination temperature to 800°C, and the calcination time to 2h.
2. The method for preparing a superstructured carbon nanotube absorbing material according to claim 1, characterized in that: In the first step, the usage ratio of ammonium molybdate tetrahydrate to nitric acid solution is 0.05-0.09 g: 17-21 mL.
3. The method for preparing a superstructured carbon nanotube absorbing material according to claim 1, characterized in that: In the second step, the usage ratio of anhydrous ethylenediamine, N,N-dimethylformamide and pyromellitic anhydride is 0.576-0.580 g: 58-62 mL: 2.119-2.123 g.
4. The method for preparing a superstructured carbon nanotube absorbing material according to claim 1, characterized in that: In the second step, the ultrasonic frequency is 30 KHz, and the ultrasonic time is 1-2 hours; the drying temperature is 60° C., and the drying time is 4 hours; the reflux environment is alkaline conditions, and the reflux time is 6 hours.
5. The method for preparing a superstructured carbon nanotube absorbing material according to claim 1, characterized in that: The mass concentration of the ammonia water in the third step is 6%, the dosage is 23-27 mL, and the stirring time is 12 h.
6. The method for preparing a superstructured carbon nanotube absorbing material according to claim 1, characterized in that: In the third step, the drying temperature is 70° C. and the drying time is 6 h; the washing is carried out using deionized water and ethanol in sequence.
Citation Information
Patent Citations
Preparation method of graphene-enhanced biomass porous carbon electromagnetic wave-absorbing material
AU2020102003A4
Transition metal sulfide-silicon carbide fiber multi-scale reinforcement reinforced resin-based structure wave absorbing material and preparation method thereof
CN108559262A